As narrativas midiáticas sobre vítima na enchente de 2014 no vale do Itajaí, SC. Trauma e repetição - Engbrecht, Simone (2017)
Inspired by the challenge set by Joel Birman (2006), to sustain a crossing that deconstructs bondage and the masochistic pact in the present time, we investigate the media narratives about the victim status in the flood in the region bathed by the river Itajaí-Açu, SC, of 2014 possessing as a theoretical resource the study of repetition and trauma developed inpsychoanalysis. Anthropologists Didier Fassin and Richard Rechtman (2009) formulated the term "new language of events," when they considered that events are taken in the present day as traumatic and legitimatising of victims, to name the withdrawal of the singular and subjective place of the individual due to psychopathological labels used in a generalized way. During the review of literature on the subject, the research of Paulo Vaz and Gaelle Rony (2011), based on magazine and TV reports, on events from natural catastrophes in Rio de Janeiro and where they perceivedthat the form of denunciation to the State has been changing over the last forty years. We are particularly interested in their discussion of the observation of how piety policy has been replaced by virtual victim policy, in which the victim figure is generalized to all who attend an event and are traumatized by it and which agrees with Fassin's observation (Fassin, 2002 apud VAZ; RONY, 2011) that the difference between piety and compassion isbeing undone. This research was qualitative, using the collection of documents from the newspaper A Notícia, from Joinville, SC, for having a regional and daily publication, within a month after the beginning of this flood. We collected 110 flood-related reports and the analysis of the data was performed by means of content analysis, according to Laurence Bardin (2016). The narratives pointed to the recidivism of floods in the region, but making a difference by comparing the strength of destructiveness in 2014 and other episodes, building an idea of the need for a more accurate climate forecast. In them also the call for donations for the victims was based on the proposal of solidarity offered by the culture. We understand that a break up with the use of the ideas of false protection, which can be feed by words of superficial or superfluid solidarity, becomes necessary. To disrupt banality meant that we asked ourselves about repetition, as well as the recurrence of the facts. It was the difference between Unheimliche and signal anguish: the afterwardsness, that we associate two fundamental understandings of two authors on these concepts. Birman pointed out the Unheimliche indicating the helplessness. And, according to Lacan (2005), this signal would communicate the pretension of jouissance of the other. In these narratives, the banal anguish signal that seeks the weather forecast conceals and produces a Verleugnung of a social difference. The Unheimliche, if it existed, in the readers, would create this possibility in perceiving the differences. The flood of contradictory narratives is directed at those who read something as if it were a signal anguish. However, the Unheimliche can also point to a confusion of narratives, in the manner of confusion of languages, according to Ferenczi (1992), and, from Birman (2006), to cross that desert of contradictions and denials and to grow fraternal linkages enlightened by the similarity and grounded in love bonds.